5-2(0)=y

Simple and best practice solution for 5-2(0)=y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(0)=y equation:


Simplifying
5 + -2(0) = y

Multiply -2 * 0
5 + 0 = y

Anything times zero is zero.
5 + 0 = y

Combine like terms: 5 + 0 = 5
5 = y

Solving
5 = y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
5 + -1y = y + -1y

Combine like terms: y + -1y = 0
5 + -1y = 0

Add '-5' to each side of the equation.
5 + -5 + -1y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -1y = 0 + -5
-1y = 0 + -5

Combine like terms: 0 + -5 = -5
-1y = -5

Divide each side by '-1'.
y = 5

Simplifying
y = 5

See similar equations:

| 5(x^2-4)+4=45 | | 6(4+2a)=72 | | 6(2k-8)=0 | | 5-2(2)=4 | | 4(1+2x)=76 | | 5(6-6d)=-60 | | 7(1+4d)=147 | | 3(1+7a)=-144 | | 2(3m+4)=62 | | 3tan^3x-tanx=0 | | x^2-8x+k=0 | | 6(-2)=-3y | | 3(7+2b)=75 | | 6(-2w-10)=60 | | 4(6+5t)=204 | | 2(4w+5)=34 | | 7(-5b+2)=49 | | 2(-7+6k)=-98 | | 6(0)=-3y | | 6(2)=-3y | | 7(3-6k)=-105 | | 3(4k+10)=54 | | 2(5-7d)=24 | | 7(-6-3w)=-210 | | 7(6-4b)=-154 | | 11+2x=55+3x | | .3x-9=.16x-4 | | 6(4t+9)=78 | | 6(7d+5)=240 | | 2(-6n+9)=-6 | | 4(-7-6a)=-148 | | 5(3+7d)=400 |

Equations solver categories